Modelling biocompatible ionic liquids based on organic acids and amino acids: challenges for computational models and future perspectives. Issue 18 (16th April 2021) - Bodo, Enrico
Abstract : From isolated molecules to the bulk phase: building models of biocompatible ionic liquids. Abstract : In this short review I shall highlight the basic principle and the difficulties that arise in attempting the computational modeling of seemingly simple systems which hide an unexpected complexity. Biocompatible ionic liquids which are based on the coupling of organic or amino acid anions with metabolic cations such as cholinium are the target of this review. These substances have been the subject of intense research activities in the last few years and have attracted the attention of computational chemists. I shall show that the computational description of these substances is far from trivial and requires the use of sophisticated techniques in order to account for a surprisingly rich chemistry that is due to several phenomena such as polarization, charge transfer, proton transfer equilibria and tautomerization reactions.